The effect of watermelon frost on prostaglandin E2 (PGE2) in inflamed pulp tissue (in vitro study) - Dennis Dennis; Trimurni Abidin (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Pulp inflammation can be marked by the increase of prostaglandin E2(PGE2) level compared to normal pulp. The increase of PGE2 may lead to vasodilatation, increase of vascular permeability, pain and bone resorption. Watermelon frost has been well known in Chinese society for pain relief and inflammation in oral cavity and teeth. Purpose: The aim of this study was to investigate that watermelon frost can be used to decrease the PGE2 level. Method: 27 samples of pulp tissues used in this in-vitro study, were extirpated from the patients’ teeth with symptomatic irreversible pulpitis referred to clinic of Conservative Dentistry, RSPGM Faculty of Dentistry, USU. Trial materials were applied to 27 samples i.e. watermelon frost as a trial material and commercial watermelon frost and eugenol to observe their effect on PGE2. PGE2 level of each material was detected through ELISA method by measuring and comparing the absorbance reading of the wells of the samples against standards with a micro plate reader at W1 = 650 nm and W2 = 490 nm. Result: The result showed the biggest effect was found in the third group (eugenol), mean 4.6933, followed by the first group (watermelon frost as a trial material), mean 18,1578 then the second group (commercial watermelon frost), mean 82,2689. OneWay ANOVA revealed that there were significant differences among all trial materials (p < 0.001) on PGE2 level. Conclusion: This study demonstrated that watermelon frost can be used to decrease the PGE2 level in inflamed pulp tissue and led to the acceptance of traditional medicine and natural products as an alternative form of dental care.